IMPLEMENTASI CORAL REEF REHABILITATION AND MANAGEMENT PROGRAM-CORAL TRIANGLE INITIATIVE (COREMAP-CTI) DALAM KONSERVASI PERAIRAN DAERAH DI BATAM KEPULAUAN RIAU - Riri Mailanti; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this research is to explain about Implementation of Coral Reef Rehabilitation and Management Program-Coral Triangle Initiative (Coremap-CTI) in Batam, Riau Archipelago. Coremap-CTI is a program implemented by the Ministry of Marine Affairs and Fisheries of Indonesia in cooperation with Asian Development Bank (ADB) as a fund donor in Batam City area. The purposes of Coremap – CTI programme are to keep coral ecosystems and improve the society’s prosperity of the area.This research is using perspective Green Thought, unit of analysis is international system, and also using concept of sustainable development, conservation and political ecoligy. Sources were obtained through literature review from journals, books, reports, and internet to explain Coremap-CTI. Researcher also did an interview from informant that conduct for the program.This research indicated that implementated Coremap-CTI programme influencing the public knowledge of the importance of protecting coral reefs and avoid illegal fishing. The results also show that the societies of conservation area don’t have significant development for economyKeywords: Coral Reef Rehabilitation and Management Program-Coral Triangle Initiative (Coremap-CTI), Conservation, Political Ecology, Batam